Roman pottery from Tilurium -Project TILURIUM - Šimić-Kanaet, Zrinka (2010)
Archaeological excavations of Roman legionary camp Tilurium revealed the total of 31.918 movable findins.25.990 of those, or 81, 48% of the total number of findings, were classified as ceramics.Ceramics is the main source of the information about everyday life in the Roman military camp Tilurium.Roman pottery from Tilurium is standard ceramic material which has also used in other military camps.There were three chronologically-typological stages which were recognized as relevant in dating Tilurium pottery.This analysis has enabled us to date ceramic artifacts from Tilurium within the timeframe ranging the end of 1.st.century B.C. until 5th century A.D.
Prikani rezultati proizišli su iz znanstvenog projekta (Rimski vojni logori u Hrvatskoj)provođenog uz potporu Ministarstva znanosti, obrazovanja i športa Republike Hrvatske.
Projekt MZOS
ENG